Markets, rights and power in Australian social policy - Meagher, Gabrielle (Public and Social Policy, 2015)
The provision of social services in Australia has changed dramatically in recent decades. Governments have expanded social provision without expanding the public sector by directly subsidising private provision, by contracting private agencies, both non-profit and for-profit, to deliver services, and through a number of other subsidies and vouchers. Private actors receive public funds to deliver social services to citizens, raising a range of important questions about financial and democratic accountability: 'who benefits', 'who suffers' and 'who decides'. This book explores these developments through rich case studies of a diverse set of social policy domains. The case studies demonstrate a range of effects of marketisation, including the impact on the experience of consumer engagement with social service systems, on the distribution of social advantage and disadvantage, and on the democratic steering of social policy.